2019
DOI: 10.1002/aenm.201901519
|View full text |Cite
|
Sign up to set email alerts
|

LiTFSI‐Free Spiro‐OMeTAD‐Based Perovskite Solar Cells with Power Conversion Efficiencies Exceeding 19%

Abstract: To date, the most efficient perovskite solar cells (PSCs) employ an n–i–p device architecture that uses a 2,2′,7,7′‐tetrakis(N,N‐di‐p‐methoxyphenyl‐amine)‐9,9′‐spirobifluorene (spiro‐OMeTAD) hole‐transporting material (HTM), which achieves optimum conductivity with the addition of lithium bis(trifluoromethane)sulfonimide (LiTFSI) and air exposure. However, this additive along with its oxidation process leads to poor reproducibility and is detrimental to stability. Herein, a dicationic salt spiro‐OMeTAD(TFSI)2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 52 publications
1
95
0
Order By: Relevance
“…Li‐TFSI is notorious for its hydrophilic nature, which in turn attracts water in the device and degrades the perovskite layer. [ 78 ] Different studies have shown that the degradation mechanism of the perovskite layer at high temperature and ambient conditions is initiated from spiro‐OMeTAD. [ 79–81 ] It is also reported in these studies that the mechanism starts from the ingress of iodide ions from the perovskite layer to the HTL.…”
Section: Stability Of Other Layersmentioning
confidence: 99%
“…Li‐TFSI is notorious for its hydrophilic nature, which in turn attracts water in the device and degrades the perovskite layer. [ 78 ] Different studies have shown that the degradation mechanism of the perovskite layer at high temperature and ambient conditions is initiated from spiro‐OMeTAD. [ 79–81 ] It is also reported in these studies that the mechanism starts from the ingress of iodide ions from the perovskite layer to the HTL.…”
Section: Stability Of Other Layersmentioning
confidence: 99%
“…PDPP-[T] 2 -EDOT (M n = 19 420 g mol −1 ; T m = 334 °C in flash DSC at 200 K s −1 ) and Spiro-OMeTAD(TFSI) 2 were synthesized using procedures known in the literature and described in the Supporting Information. [19][20][21][22] Spiro-OMeTAD(TFSI) 2 was characterized using X-ray photoelectron spectroscopy (XPS) and UV-vis spectroscopy. See Figures S1 and S2 in the Supporting Information for its atomic and chemical composition.…”
Section: Unlike the Conventional P-doping Of Organic Semiconductors (mentioning
confidence: 99%
“…20 Very recently, work from Bach et al has boosted device PCEs to over 19% in the absence of LiTFSI together with an increased device stability attributed to a more hydrophobic HTM layer. 24 In summary, single crystals of doubly oxidized Spiro-OMeTAD were grown and structurally characterized. Based on the structure information, frontier orbitals and electronic band structures were modelled and compared with neutral Spiro-OMeTAD.…”
mentioning
confidence: 99%